OUTPATIENT CARDIAC REHABILITATION OF PATIENTS AFTER CORONARY ARTERY REVASCULARIZATION, PROBLEMS AND PROSPECTS - Ovdii, M.A. (The Ukrainian Scientific Medical Youth Journal, 2017)
Ishemic heart disease (IHD) is the main cause of death in Ukraine and throughout the world. The use of progressive surgical and modern medications has provided hope for an improvement in the situation. But WHO’s predictions about this problem are quite disappointing. Cardiac rehabilitation is still in the shadow of surgical and medical therapies.